A trajetória eduacional e profissional de um professor amazônida - Pinheiro, Antonio de Castro (Brasil, 2024)
This memorial aims to report the academic trajectory of student Antonio de Castro Pinheiro during his journey in the pedagogy circle at Faced College. And discuss the challenges and difficulties faced during this journey, especially during remote teaching during the Covid-19 pandemic. Reflecting on the importance of supervised internships in the training of future pedagogues and what experiences will contribute to my commitment to education in my professional life.